Konsep pendidikan anak menurut Ibnu Sina dan Al-Ghazali: tinjauan filosofis - Ahmad Romadhon; Ahmad Mustofa; Paris Abdillah; Benny Prasetiya (Sekolah Tinggi Agama Islam (STAI) AL-IKHLAS DAIRI SIDIKALANG, 2026)
This study explores the philosophical concept of child education according to Ibn Sina (Avicenna) and Al-Ghazali, two prominent figures in classical Islamic intellectual tradition. The research aims to examine their educational philosophies, emphasizing their epistemological foundations, moral objectives, and pedagogical orientations. Employing a qualitative library research design with content analysis, this study analyzes primary texts such as Kitab al-Najat, Risalah fi al-Tarbiyah, and Ihya’ Ulum al-Din, alongside secondary sources. Findings reveal that both thinkers view education as a comprehensive process aimed at nurturing the intellectual, moral, and spiritual dimensions of the child in harmony with divine purpose. Ibn Sina’s approach emphasizes rational and empirical cultivation of the intellect, while Al-Ghazali stresses spiritual purification and moral habituation grounded in revelation. Despite differing in emphasis, both share the ultimate goal of forming the insan kamil (perfect human). Theoretically, this study contributes to understanding Islamic educational philosophy as an integration between reason and faith, while practically, it provides insight for contemporary Islamic pedagogy to balance cognitive development and moral education. This philosophical synthesis remains relevant in addressing the moral and intellectual challenges of modern education.